Silkworm Growth and Silk Yield under Changing Climatic Conditions: Challenges and Adaptations - Susikaran S; Karthick Mani Bharathi B; Allwin Loveson; V Vasanth; S Navanneetha Krishnan; Kiruthika C (International Journal of Insects, 2024)
Climate change is emerging as a critical factor affecting agriculture and sericulture industries worldwide. Rising global temperatures, shifting rainfall patterns, and the growing frequency of extreme weather events present ever challenges to the growth and productivity of silkworms (Bombyx mori L.). Silkworms are extremely sensitive to environmental conditions like temperature, humidity, and photoperiod, all altered by climate change. Higher temperatures can accelerate silkworm metabolism, reduce silk yield, and increase susceptibility to diseases, and lead to developmental abnormalities. In addition, changes in rainfall patterns and shifts in soil moisture affect the growth and nutritional quality of mulberry’s plant (Morus sp.), the primary food source for silkworms. As a result, poor-quality mulberry leaves led to reduced silkworm health and lower silk output. Increased disease incidence, pest pressure, and water scarcity further compounded by climate variability will continue to threaten the sustainability of the sericulture industry. However, recent research highlights adaptive strategies, such as breeding climate-resilient silkworm varieties thereby improving mulberry cultivation practices, implementing integrated pest management (IPM) and using controlled rearing environments as potential mitigations. This abstract summarizes the critical effects of climate change on silkworm biology, mulberry plantations, and silk production while also emphasizing the need for continued research, innovation, and policy intervention to secure the future of the sericulture industry in a rapidly changing climate.
Keywords: Climate change; sericulture; silk yield; silkworm biology; silkworm health